FOGSYS: a system for the implementation of StaaS service in a fog computing using embedded platforms. (30th April 2021) - Machado, José Dos Santos; Silva, Danilo Souza; Fontes, Raphael Silva; Menezes, Adauto Cavalcante; Moreno, Edward David; Ribeiro, Admilson De Ribamar Lima
This work presents the concept of Fog Computing, its theoretical contextualisation and related works, and develops the FogSys system with the main objective of simulating, receiving, validating and storing data from IoT devices to be transferred to Cloud Computing, serving as a Fog Computing to provide the StaaS (Storage as a Service) service. The results showed that the implementation of this service in devices of embedded systems can be a good alternative to reduce the problems, in this case, the storage of data, which are faced currently by IoT devices.